I'd like to prove the following proposition: $$ \lim_{n\rightarrow\infty} a_n = \infty \Rightarrow \lim_{n\rightarrow\infty} b_n = \infty \\ \text{where}\;b_n = \dfrac{1}{n}\sum_{k=1}^{n}a_k, $$

but my proof was stuck. Would you tell me how should I finish the proof?

Suppose $\lim_{n\rightarrow\infty} a_n = \infty$ ($\forall\epsilon\in\mathbb{R},\,\exists N\in\mathbb{N},\,\forall n\in \mathbb{N},\,n\geq{}N\Rightarrow a_n > \epsilon$), then I'll prove $\lim_{n\rightarrow\infty} b_n = \infty$.

Let $\epsilon\in \mathbb{R}$. For $n\geq N$, $b_n=\dfrac{1}{n}\sum_{k=1}^{N}a_k+\dfrac{1}{n}\sum_{k=N+1}^{n}a_k>\dfrac{1}{n}\sum_{k=1}^{N}a_k+\dfrac{n-N}{n}\epsilon=\dfrac{1}{n}\sum_{k=1}^{N}(a_k-\epsilon) + \epsilon,$ from the supposition.

In order to prove $b_n>\epsilon$, I only prove $\dfrac{1}{n}\sum_{k=1}^{N}(a_k-\epsilon)\geq0$ ($N_0$ exists and for all $n\geq N_0$), but $a_n-\epsilon$ for $n < N$ can't be proved. What's wrong? And how do I let $N_0$?


2 Answers 2


Note that $x_n > y_n \implies \liminf x_n \geqslant \liminf y_n$ and for all $\epsilon > 0$

$$\limsup_{n \to \infty} b_n \geqslant \liminf_{n \to \infty} b_n \geqslant \lim_{n \to \infty} \frac1{n}\sum_{k=1}^Na_k + \lim_{n \to \infty}(1 - N/n)\epsilon = \epsilon.$$

Hence, $\lim b_n = \limsup b_n = \liminf b_n = + \infty.$

Alternatively, with $N$ fixed,

$$\lim_{n \to \infty} \frac1{n}\sum_{k=1}^Na_k = 0 , \\ \lim_{n \to \infty} (1 - N/n) = 1,$$

and, for $n$ sufficiently large

$$\frac1{n}\sum_{k=1}^Na_k > -\epsilon/4, \\ (1 - N/n) > 1/2,$$ and

$$b_n > \frac1{n}\sum_{k=1}^Na_k + (1 - N/n)\epsilon > -\epsilon/4 + \epsilon/2 = \epsilon/4$$


You just need to go than further $N$.

Let $A > 0$ be arbitrary ($\epsilon$ usually denotes a small quantity, I prefer to use $A$ instead).

Since $a_n\to \infty$, there is some $N$ such that $n\geq N\implies a_n\geq 2A$.

Even if it's out of the blue at the moment, let $\displaystyle N'=\max(1+\lfloor \frac{\sum_{k=1}^N (2A-a_k)}{A}\rfloor,0).$

Let $N''=\max (N,N')$ and consider some $n\geq N''$.

Note that$$\begin{align}\sum_{k=1}^n a_k&\geq \sum_{k=1}^{N^{''}} a_k + (n-N'')2A \;\; \text{because}\; n\geq N \\ &= An + \left(An - \sum_{k=1}^{N^{''}}(2A-a_k) \right) \\ &\geq An \;\; \text{because}\; n\geq N'\end{align}$$

Hence $\frac {1}n \sum_{k=1}^n a_k \geq A$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.